Economics of Sludge and Water Effluent Management of Wastewater Treatment Plant - Lekhak, Basant; Khatri, Mukti Bahadur; Bhatt, Dinesh Prasad (Journal of Science and Technology, 2024)
The Guheshwori Wastewater Treatment Plant (GWTP) was used for the study work. The main objective of the research work was to analyze the economic benefits of sludge and water effluent management of the Wastewater Treatment Plant (WWTP). The Cost Benefit Analysis methodology was used and analyzed to meet the research objectives. The Wastewater treatment plant has significant environmental benefits as well as monetary values that can be generated from water effluent, sludge effluent, and plant visit fares, which indicates the revenue generation from the wastewater treatment plant. This study takes a ground-breaking strategy to economically value wastewater treatment in Nepal. A helpful indication of the viability of wastewater treatment will be the comparison of the benefits of WWTP with the operating costs of the treatment process. On a dry mass basis, the finished sludge had a total nitrogen content of 3.58 percent, a total phosphorus content of 1.54 percent, and a potassium content of 0.15 percent. After pathogen reduction sludge can be used in agricultural fields as fertilizer leading to high monetary values for GWTP. Plant visit fares from the visitors also can generate monetary value. Similarly, water effluent can be used in watering the parks, irrigation, and cleaning, and after turbidity reduction can be used in concreting and curing. The Guheshwori Waste Water Treatment Plant requires a yearly total of around NRs. 4,49,94,639 to operate. If we merely sale 5% of the treated water NRs. 94,03,130, 10% of the treated water NRs. 1,88,08,085, 50% of the treated water NRs. 9,40,28,380, and 100% of the treated water NRs. 18,80,61,870 can be generated. From the GWTP wastewater treatment plant’s sludge, 57,34,202 may be produced yearly. There is a potential income generation of about NRs. 12,02,500 from the plant visit fares. To close these disparities, Government of Nepal (GoN) must enact legislation on the optimal use of WWTP effluent, the protection of water sources, public health, and environmental economics. The welfare concept of economics concept states the maximum utilization of the reuse of the resources of the effluents from the Guheshwori Wastewater Treatment Plant, NBV>1 can be achieved from an environmental economics viewpoint alongside achieving Sustainable Development Goals SDGs Goals 6, 8, and 11.